Tackling malnutrition in children through the inclusion of dried small fish powder in their diets - Gaikwad, Amar; Panemangalore, Arun; Ratha, Baishnaba C. (WorldFish, 2022)
Assam continues to grapple with high food insecurity and malnutrition levels, especially among young children and pregnant-lactating women despite its vast resources. Increasing the accessibility, availability and affordability of aquatic foods among consumers will lead to an increase in aquatic foods consumption that will reduce malnutrition and hidden hunger that many nations are experiencing. WorldFish, through the Matsya Paripusti project, aims to improve the nutrition profile of malnourished children and their physical and mental growth by advocating for the inclusion of nutrient-rich dried small fish powder in their mid-day meal program at the Anganwadi centers.